Investigation of the structural, optical and dielectric properties of highly (100)-oriented (Pb0.60Ca0.20Sr0.20)TiO3 thin films on LaNiO3 bottom electrode - Pontes, D. S. L.; Pontes, F. M. [UNESP]; Chiquito, A. J.; Longo, E. [UNESP] (Elsevier B.V., 2014)
Highly (100)-oriented Pb0.60Ca0.20Sr0.20TiO3/LNO/LAO structure was fabricated using a chemical deposition process via spin-coating technique. XRD revealed that both LNO and Pb0.60Ca0.20Sr0.20TiO3 films grown on LAO(100) substrate and LNO/LAO(100) structure were crystallized to be highly (h00)-oriented, respectively. AFM images revealed smooth surfaces, spherical-shaped grains and a crack-free surface with a roughness of about 3-7 nm. The tetragonal perovskite phase was confirmed by Raman spectroscopy for Pb0.60Ca0.20Sr0.20TiO3/LNO/LAO and Pb0.60Ca0.20Sr0.20TiO3/LAO structures. The optical transmittance of 340 nm thick Pb0.60Ca0.20Sr0.20TiO3 films on a LAO(100) substrate exhibited an average transmittance above 80% in the wavelength range of 500-1000 nm and an optical band gap E-g of 3.56 and 2.87 eV for the direct and indirect transition processes, respectively. The Pb0.60Ca0.20Sr0.20TiO3/LNO/LAO structure has a hysteresis loop with remnant polarization, P-r, of 12 mu C/cm(2), and a coercive field, E-c, of 46 kV/cm for an electric field at 370 kV/cm along with a dielectric constant over 1200. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Thin films; Chemical synthesis; Optical properties; Ferroelectric properties